Cloning and functional identification of sesquiterpene synthase gene NjTPS2 in Nardostachys jatamansi DC - Hao, ZhiYu; Peng, LiJun; Hu, YueYing; Wu, XunJian; Li, YuanYuan; Zhang, JunCheng; Tang, XiaoHui; Pei, Jin; Chen, Jiang (Frontiers in Plant Science, 2026)
BackgroundNardostachys jatamansi DC is a plant of the Valerianaceae. As an economic crop, it is used in traditional Chinese and Tibetan medicines as well as in spices. The sesquiterpenoids in this plant are the main components that contribute to its medicinal value; however, the current understanding of their biosynthesis pathway remains unclear.MethodsVolatile components of N. jatamansi were detected via metabolomics. Candidate sesquiterpene synthase genes were screened based on transcriptome sequencing results. Quantitative real-time PCR (qRT-PCR) was employed to detect the differential expression of the candidate genes in different tissues of N. jatamansi, so as to preliminarily verify the functions of the candidate genes. Finally, the yeast expression system and tobacco transient expression system were utilized to verify the function of the gene NjTPS2.ResultsA total of 736 compounds were detected through metabolomic analysis, which were classified into 16 categories. Among them, there were 211 terpenoid compounds and 138 sesquiterpenoid compounds. By performing RNA-seq on N. jatamansi, 14.29 Gb of clean data was obtained, and 9 sesquiterpene synthase genes were successfully screened out, which belong to four subfamilies, namely TPSa, TPSb, TPSc, and TPSe/f. The NjTPS2 gene in the TPSb subfamily was cloned and subjected to bioinformatics analysis. The full length of its CDS (Coding Sequence) is 1212 bp, and domain analysis revealed that it has two core catalytic domains for terpenoids: Terpene synth C and Terpene synth. The results of quantitative real-time PCR (qRT-PCR) showed that NjTPS2 had the highest expression level in roots, while its expression levels in other tissues were relatively low. Functional verification of NjTPS2 was conducted using the tobacco transient expression system and yeast expression system, and it was found that this gene could produce sesquiterpenoids.ConclusionOur results confirm NjTPS2 possesses the functional activity of a sesquiterpene synthase. It provides genetic resources for elucidating the molecular mechanism underlying the quality formation of N. jatamansi, as well as for the biosynthesis of sesquiterpenoids in N. jatamansi and the breeding of high-quality N. jatamansi varieties.